2021
DOI: 10.1249/jsr.0000000000000831
|View full text |Cite
|
Sign up to set email alerts
|

ACSM Expert Consensus Statement on Weight Loss in Weight-Category Sports

Abstract: Weight-category sports are defined by the requirement of a weigh-in before competition to provide performance equity and reduced injury risks by eliminating size discrepancies. Athletes in these sports try to gain a theoretical advantage by competing in weight divisions that are lower than their day-to-day body mass (BM), using a combination of chronic strategies (body-fat losses) and acute manipulations over a period of hours to days before weigh-in (“making weight”). Strategies to support safer practices inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 94 publications
2
72
0
1
Order By: Relevance
“…Common to all contexts, this phase of nutrition support should centre around rehydration and endogenous glycogen content restoration, whilst also considering the potential for gastrointestinal distress. Given a thoroughly detailed examination of this area is beyond the scope of this article, readers are again encouraged to see Reale, Slater, and Burke (2017b) and Burke et al (2021) for an in-depth overview, which provides practical considerations pertinent to refeeding and recovery in weight making athletes of both sexes.…”
Section: Refeed and Recovery Strategies Post Weigh Inmentioning
confidence: 99%
“…Common to all contexts, this phase of nutrition support should centre around rehydration and endogenous glycogen content restoration, whilst also considering the potential for gastrointestinal distress. Given a thoroughly detailed examination of this area is beyond the scope of this article, readers are again encouraged to see Reale, Slater, and Burke (2017b) and Burke et al (2021) for an in-depth overview, which provides practical considerations pertinent to refeeding and recovery in weight making athletes of both sexes.…”
Section: Refeed and Recovery Strategies Post Weigh Inmentioning
confidence: 99%
“…Recently, the ACSM published the most comprehensive position statement on weight loss yet [ 10 ], this time extending its recommendations to other weight-sensitive sports (lightweight rowing, horse racing, skiing, skating, and gymnastics). In this publication, we will focus on weight loss recommendations pertaining only to combat sports.…”
Section: Calls For Actionmentioning
confidence: 99%
“…Experts have suggested that RWL comprising up to 2–3% body mass has insignificant drawbacks, particularly if an optimal recovery period is provided. However, a weight loss ˃3% body mass may have substantial negative effects on both health and performance as outlined within this position statement [ 10 ]. It appears that athletes are cognizant that RWL may hinder their overall performance but they consistently engage in RWL to compete in a lower weight class, believing they may have a physiological or psychological advantage, especially when there is substantial time to recover and even retain pre-RWL weight [ 10 ].…”
Section: Calls For Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combat athletes compete in designated weight classes that are intended to promote fair competition by matching opponents of similar stature and body mass. As such, these athletes typically engage in chronic (CWL) and acute weight loss (AWL) strategies (referred to as "making weight") that largely comprise prolonged periods of energy restriction and acute episodes of dehydration (Burke et al, 2021). When making weight, combat athletes often partake in training camps that typically range in duration from 4-12 weeks where a large part of the training period is completed in conditions indicative of sub-optimal energy availability (Kasper et al, 2019;Langan-Evans et al, 2020;Morton et al, 2010).…”
Section: Introductionmentioning
confidence: 99%